Mudik Myth in The Baudrillard’s Simulacra Perspective - Rima Agristina; Leonnard Ong (International Journal of Business Studies, 2021)
The research aims to review literatures and discuss regarding the myths and simulacra of homecoming. The research conducted is normative research or study literature, using a variety of literature (a semiotic approach) that discusses regarding myths, simulacras and simulations. This semiotic approach is used with based on the idea that the notion of myth in this study using the understanding of myth according to Barthes's view of the myth as semiological system of the second order (simulacra) of Baudrillard. Homecoming can be understood as a need for social existence and human legitimacy. Re-growth of existence in a society carrying out homecoming can be done by understanding the characteristics of the homecoming perceived by society. This respect or social legitimacy is usually explained because of positive word of mouth for being an urbanity. By understanding the homecoming’s character perceived by society, the need for existence through “mudik” can put into other activities so that people carry out to a more rational homecoming regularly. Because the research is in the from of literature and qualitative study, it is necessary to carry out further research on public perceptions regarding homecoming by considering cultural or ethnic factors, and also favorable behavioral intentions consisting of positive word of mouth.